Comparative analysis of geothermal and reservoir numerical simulation methods - GAI Changcheng, LI Hongda, REN Lu, CAO Wei, HAO Jie (Youqicang pingjia yu kaifa)
Geothermal energy and petroleum are both vital subsurface energy resources. Numerical simulation of geothermal and reservoir systems is a key technology for evaluating and optimizing the development and utilization of these resources, playing an essential guiding role in the energy sector. By comparing the foundational mathematical models, numerical methods, and case studies of geothermal and reservoir simulations, this study highlights the similarities and differences in their application to the development of these two energy sources. In terms of simulation methods, geothermal numerical simulations focus on heat conduction and geothermal field variation, whereas reservoir numerical simulations emphasize fluid dynamics and the oil extraction process. Regarding simulation results, geothermal simulations are used for geothermal resource development planning and the optimization of key production parameters, while reservoir simulations are primarily applied to reserve estimation, injection-production parameter optimization, and well production management. This comparative analysis provides theoretical and practical guidance for research and applications in geothermal energy and petroleum engineering, promoting the efficient and sustainable utilization of both energy resources.